Gut microbiome approaches to treat obesity in humans - Bianchi, Fernanda [UNESP]; Duque, Ana Luiza Rocha Faria [UNESP]; Saad, Susana Marta Isay; Sivieri, Katia [UNESP] (Springer Nature, 2019)
The rising worldwide prevalence of obesity has become a major concern having many implications for the public health and the economy. It is well known that many factors such as lifestyle, increased intake of foods high in fat and sugar and a host’s genetic profile can lead to obesity. Besides these factors, recent studies have pointed to the gut microbiota composition as being responsible for the development of obesity. Since then, many efforts have been made to understand the link between the gut microbiota composition and obesity, as well as the role of food ingredients, such as pro- and prebiotics, in the modulation of the gut microbiota. Studies involving the gut microbiota composition of obese individuals are however still controversial, making it difficult to treat obesity. In this sense, this mini-review deals with obesity and the relationship with gut microbiota, summarising the principal findings on gut microbiome approaches for treating obesity in humans.
Keywords: Gut microbiota; Management of obesity; Obesity